Giant pseudocyst of the spleen: A case report and review of the literature - Kalinova K (Wolters Kluwer Medknow Publications, 2005)
Splenic cysts are rare lesions. Primary cysts have a cellular lining that can be caused by congenital events or parasitic infection (Echinococcus). Secondary cysts have no cellular lining and may be of hemorrhagic, serous, inflammatory, or degenerative origin. We report a case of pseudocyst treated successfully by splenectomy, and we review the literature.